Acoustic aspects of a radial diffuser - KRASINSKI, J. De; WAWSZCZAK, W.; SUN, S. (Archives of Acoustics, 1986)
The flow in a supersonic radial-diffuser is investigated experimentally and the results of the experiments are discussed in the light of existing theories From such an analysis it is concluded that a better understanding of this particular diffuser, which can be used as a sound attenuator, may lead to other applications in the field of propulsive units and jet flows.